2005
DOI: 10.1093/jn/135.8.1960
|View full text |Cite
|
Sign up to set email alerts
|

Long-Chain (n-3) Polyunsaturated Fatty Acids Are More Efficient than α-Linolenic Acid in Improving Electroretinogram Responses of Puppies Exposed during Gestation, Lactation, and Weaning

Abstract: Long-chain PUFAs (LCPUFAs) are essential for proper neural and retinal development in many mammalian species. We investigated puppies born to dogs fed diets containing varying amounts of vegetable and marine (n-3) fatty acids during gestation/lactation. The fatty acid compositions of dogs' milk and puppy plasma phospholipids were evaluated, and electroretinographic responses of the young dogs were determined after they were weaned to the same diets. Dogs' milk fatty acid composition reflected the diets fed dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
40
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
3
3
3

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(43 citation statements)
references
References 47 publications
3
40
0
Order By: Relevance
“…Similar enrichments of EPA and DPAn-3 have been observed in human plasma using a 4 week feeding period [24]. For that matter, this phenomenon has been observed in humans and various other animal species (reviewed in [25]) and is consistent with other evidence that plasma enrichment of DHA after ALA supplementation is less efficacious than providing smaller dietary amounts of preformed DHA per se [25,26]. It should be noted that studies in rats have shown the conversion of ALA all the way to DHA to be effective in liver and plasma [27].…”
Section: Discussionsupporting
confidence: 82%
“…Similar enrichments of EPA and DPAn-3 have been observed in human plasma using a 4 week feeding period [24]. For that matter, this phenomenon has been observed in humans and various other animal species (reviewed in [25]) and is consistent with other evidence that plasma enrichment of DHA after ALA supplementation is less efficacious than providing smaller dietary amounts of preformed DHA per se [25,26]. It should be noted that studies in rats have shown the conversion of ALA all the way to DHA to be effective in liver and plasma [27].…”
Section: Discussionsupporting
confidence: 82%
“…Supplementation of female dogs with ALA during gestation and lactation does not result in increased amounts of DHA in canine milk. 33,34 …”
Section: Discussionmentioning
confidence: 99%
“…Although most of the milk replacers contained similar or higher ALA concentrations, compared with dog milk, ALA supplementation of both gestating dogs and growing puppies does not have equivalent benefits to supplementing with DHA directly when it comes to retinal function; therefore, having similar concentrations of ALA in milk replacers, compared with dog milk, may be of little value, compared with similar concentrations of EPA and DHA. 34 More data are needed, but current research suggests that puppies may benefit from supplementation of DHA (but not necessarily ALA) to at least the concentrations found in the milk of domestic dogs consuming diets lower in total n-3 fatty acids.…”
Section: Discussionmentioning
confidence: 99%
“…They regulate several functions of the body, including inflammation, 25 which, according to current knowledge, is involved in the development of disorders affecting vision. 37 Sea buckthorn seed and pulp oils are rich sources of tocopherols and tocotrienols (Table 48.1). 30 Oral intake of combined linoleic and γ-linolenic (18:3n-6) acids has been shown to relieve dry eye.…”
Section: Bioactive Compounds Of Sea Buckthorn Berrymentioning
confidence: 99%